CCSP Cert Prep: 3 Cloud Platform and Infrastructure Security Audio Review. - Chapple, Mike (linkedin.com, 2020)
Study for the CCSP exam when you're on the go. This audio-only course reviews key concepts covered in the third exam domain: Cloud Platform and Infrastructure Security.